Thoracic surgeons, mathematics, and statisticians: a new multidisciplinary team? - Bertolaccini, Luca; Pardolesi, Alessandro; Solli, Piergiorgio (Journal of Visualized Surgery, 2017)
Thoracic surgery is a field where the researchers, from data and techniques derived from more disciplines, are combined to solve problems where solutions are beyond the scope. Mathematical and physical science could play a significant role in thoracic surgery because sometimes issues could be resolved using mathematical techniques (1).